METHODS OF WORKING WITH CHILDREN WITH VISUAL PROBLEMS STUDYING IN INCLUSIVE EDUCATION - Zulaikho Khamidullaevna Khusnuddinova (Web of Journals Publishing, 2023)
The article discusses methods of working with children with vision problems studying in inclusive education.
Keywords: method, work, children, problems, vision, inclusive education.